BLOCK HF: how far does it extend indications for cardiac resynchronization therapy?. Issue 4 (April 2016) - Boriani, Giuseppe; Ziacchi, Matteo; Diemberger, Igor; Biffi, Mauro; Martignani, Cristian; Leyva, Francisco
Abstract : The Biventricular versus Right Ventricular Pacing in Heart Failure Patients with Atrioventricular Block (BLOCK HF) trial, published in April 2013 [Curtis AB, Worley SJ, Adamson PB, et al ; Biventricular versus Right Ventricular Pacing in Heart Failure Patients with Atrioventricular Block (BLOCK HF) Trial Investigators. Biventricular pacing for atrioventricular block and systolic dysfunction. N Engl J Med 2013; 368:1585–1593], explored whether cardiac resynchronization therapy (CRT) was superior to conventional pacing in patients with conventional indications for pacing, left ventricular dysfunction and NYHA (New York Heart Association) class I–III. The trial took 8 years and a source of concern is selection bias, because participating centers had an average of two patients enrolled per center, per year. Both the internal and external validity of the trial merit some comments. BLOCK HF showed a relatively low treatment effect of CRT as compared with other CRT trials. As a matter of fact, the absolute risk reduction for death or hospitalization because of heart failure was 4.8%, in a relatively long follow-up, with a number needed to treat (NNT) of 21, much higher than the NNT of other CRT trials. We estimate that at least one third of patients in BLOCK HF could meet current indications for CRT. Moreover, the study did not consider the additional risks and costs of CRT versus conventional pacing, both having important implications for cost-effectiveness estimates. For these and other reasons, uncertainties arise as to how far BLOCK HF extends current recommendations for CRT and how much it should be implemented in daily clinical practice.